Web-Based Monitoring Application to Enhance the Effectiveness of Character Building Training (CBT) Mentoring in Higher Education - Hadi, Reza; Nora, Defla (SYNAPSI: Journal of Information Systems and Informatics Education, 2026)
Purpose of the study: This research aims to design and develop a web-based monitoring application to enhance the effectiveness of mentoring activities in the Character Building Training (CBT) program at UIN Alauddin Makassar by facilitating scheduling, digital verification, and real-time progress monitoring.Methodology: This study employs a Design and Creation approach with a Waterfall development model. Data were collected through interviews with the CBT program head, participatory observations, and literature reviews. The application was developed using PHP with CodeIgniter framework, MySQL database, and tested using Black Box testing method on three user levels: students, lecturers/mentors, and program heads.Main Findings: The resulting application successfully integrates resolution tracking, digital attendance verification replacing manual signatures, and real-time monitoring dashboard. Black Box testing confirmed all functions (login, registration, resolution checking, chat features) performed as expected without errors, enabling structured mentoring within the 40-day timeframe.Novelty/Originality of this study: This research presents a novel integrated monitoring system specifically designed for character mentoring in higher education, combining personal resolution achievement tracking, digital verification mechanisms, and two-way communication features in one platform advancing beyond general academic monitoring systems by addressing the unique needs of character value internalization processes.